Rayleigh Mixture Distribution - Rezaul Karim; Pear Hossain; Sultana Begum; Forhad Hossain (Journal of Applied Mathematics)
This paper presents Rayleigh mixtures of distributions in which the weight functions are assumed to be chi-square, 𝑡 and 𝐹 sampling distributions. The exact probability density functions of the mixture of two correlated Rayleigh random variables have been derived. Different moments, characteristic functions, shape characteristics, and the estimates of the parameters of the proposed mixture distributions using method of moments have also been provided.